2022
DOI: 10.3390/nu14061286
|View full text |Cite
|
Sign up to set email alerts
|

Utility of an Isotonic Beverage on Hydration Status and Cardiovascular Alterations

Abstract: This study determined the beverage hydration index (BHI) and postprandial cardiac autonomic activity after consuming an isotonic beverage (IB) compared to distilled water (DW). Twenty-two participants (50% female; mean ± SD; age, 27 ± 3 year; height, 169.1 ± 12.6 cm; weight, 73.3 ± 13.8 kg; BF%, 23 ± 10%) completed two experimental trials where they consumed 1 L DW or an IB; after which urine volume and cardiac autonomic activity was measured through 240 min. Cardiac autonomic activity was quantified using hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The BHI is the urine output after consumption of water divided by the urine output after beverage consumption, and it is an index commonly used to verify the hydration effect of a beverage [ 13 , 18 ]. In this study, although BHI was slightly different for each time period, ORS, SpD1, and SpD2 were higher than water from 1 to 4 h after water intake.According to Bechke et al [ 2 ], BHI was higher in sports drinks than water at 3 and 4 h after water intake, and in a study by Millard-Stafford et al [ 14 ], BHI was high in drinks containing carbohydrate and electrolyte and drinks containing dipeptide and electrolyte after 4 h after water intake, which supports the result of this study. On the other hand, Sollanek et al [ 18 ] reported that ORS showed higher BHI than water, but sports drinks did not have a statistically significant difference.…”
Section: Discussionsupporting
confidence: 90%
“…The BHI is the urine output after consumption of water divided by the urine output after beverage consumption, and it is an index commonly used to verify the hydration effect of a beverage [ 13 , 18 ]. In this study, although BHI was slightly different for each time period, ORS, SpD1, and SpD2 were higher than water from 1 to 4 h after water intake.According to Bechke et al [ 2 ], BHI was higher in sports drinks than water at 3 and 4 h after water intake, and in a study by Millard-Stafford et al [ 14 ], BHI was high in drinks containing carbohydrate and electrolyte and drinks containing dipeptide and electrolyte after 4 h after water intake, which supports the result of this study. On the other hand, Sollanek et al [ 18 ] reported that ORS showed higher BHI than water, but sports drinks did not have a statistically significant difference.…”
Section: Discussionsupporting
confidence: 90%
“…Tonicity is the ability of the extracellular solution to move water into or out of the cell by osmosis. Tonicity differs from osmolality in that it takes into account both the relative concentrations of solutes and the permeability of the cell membrane to these solutes [4].…”
Section: Introductionmentioning
confidence: 99%